A thermodynamic perspective on mammalian neural crest ingression - Clarissa C. Pasiliao; Evan C. Thomas; Theodora Yung; Min Zhu; Hirotaka Tao; Yu Sun; Sidhartha Goyal; Sevan Hopyan (Proceedings of the National Academy of Sciences, 2025)
The ingression of neural crest cells from an ectodermal to a mesodermal layer is regulated by instructive, directional cues and potentially stochastic, biophysical parameters such as differential cell adhesion and tension heterogeneity. However, a cohesive framework in which to consider how various influences contribute to ingression remains elusive. Here, we observe the cell behaviors of the murine neural crest in three dimensions over time and apply a free energy framework to more wholly understand why cells ingress. Guided by work on granular matter that provides a path by which to define the roles of stochastic mechanisms in nonequilibrium systems, we measured and manipulated biophysical parameters in vivo. The data suggest that an energy barrier to cell ingression is overcome by a combination of relatively favorable cell adhesion energies, high cell shape fluctuations, and entropic cell packing configurations. Under those conditions, cell ingression may proceed spontaneously. Recognized biophysical cues likely tilt these parameters to make the process more robust. The results imply that dissipative mechanisms which transiently disorder tissue may underlie some morphogenetic events. Variations of a thermodynamic framework can potentially be applied to integrate various inputs that drive morphogenesis in different contexts.